Use of T Cell-Based Diagnosis of Tuberculosis Infection to Optimize Interpretation of Tuberculin Skin Testing for Child Tuberculosis Contacts - KARAHASAN, AYŞEGÜL (OXFORD UNIV PRESS INC, 2009)
Background. Treatment of recent tuberculosis infection in children aged ! 2 years is essential, because of high risk of progression to disease, but diagnosis is hindered by the inaccuracy of the tuberculin skin test (TST). More-accurate T cell-based tests of infection could enhance diagnosis by optimizing interpretation of the TST results. Methods. A total of 979 child tuberculosis contacts in Istanbul underwent the TST and enzyme-linked immunospot assay. Using enzyme-linked immunospot test results as a reference standard, we assessed the effect of age and bacille Calmette-Guerin ( BCG) vaccination on the sensitivity and specificity of the TST, and we computed the optimal TST cutoff points, using receiver operating characteristic curves. Results. With a TST cutoff point of >= 10 mm, the sensitivity of the TST was 66% for children aged <2 years, which was lower than that for older children (P = .006). Specificity was 75% for BCG-vaccinated children, Pp. 006 compared with 92% for unvaccinated children (P = .001). Optimal cutoff points improved TST specificity for children with 1 BCG scar, with little loss of sensitivity. Despite the use of optimal cutoff points, TST sensitivity remained <70% for children aged <2 years, specificity remained <87% for BCG-vaccinated children aged >= 2 years, and overall accuracy was low for children with 1 BCG scar. Conclusions. Negative results of the TST cannot exclude tuberculosis infection for child tuberculosis contacts aged <2 years, which supports the use of preventive therapy regardless of the TST results for this age group. In children aged >= 2 years, the accuracy of the TST can be improved by adjustment of cutoff points for BCG-vaccinated children but remains poor for children with >1 BCG scar. This methodology can define optimal TST cutoff points for diagnosis of tuberculosis infection tailored to target populations.
Keywords: ENZYME-LINKED IMMUNOSPOT; INTERFERON-GAMMA ASSAYS; MYCOBACTERIUM-TUBERCULOSIS; PULMONARY TUBERCULOSIS; CLINICAL-PRACTICE; BCG VACCINATION; RAPID DETECTION; ENUMERATION; SENSITIVITY; EXPOSURE